Descriptive shot analysis in basketball - Raiola, G.; D'Isanto, T. (Journal of Human Sport & Exercise, 2016)
This paper tries to clarify from specific points of descriptive view, physical, technical, tactical and from that learning model, those that are the fundamental elements of the shot to basket, in order to optimize the setting and specific preparation. The physical learning is the basis of the performance, that is the skills depends from qualitative aspect. The shot is a fundamental attack in basketball, offers many points to be analyzed from technical point of view that the qualitative control model point of view, this article will try to do it on both aspect, trying to provide some elements technical and descriptive to whom refer and the description of the executive model elements characterizing the execution of the shot at basket. The aim is suggesting some technical elements to which to refer and the description of the executive model elements that characterize the execution of the shooting at basket, to improve the whole process of teaching and learning.